Influencer Marketing Strategies And The Use Of Ai Technology In Enhancing Brand Awareness: A Case Study In The Fashion Industry - Nur Afifah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This article explores the intricate dynamics of the fashion industry, focusing on PT. SRB Depot Tj. Pura. The study investigates the direct and indirect effects of Influencer Marketing and AI Technology on the Fashion Industry and Enhancing Brand. Through a comprehensive path analysis, the research reveals that Influencer Marketing significantly influences both the Fashion Industry and Brand Enhancement, both directly and indirectly through the Fashion Industry. These findings underscore the influential role of influencer-driven strategies in shaping consumer perceptions and fostering positive brand associations. However, the analysis does not provide statistically significant evidence for the direct or indirect impact of AI Technology on the Fashion Industry or Brand Enhancement within the observed context. The results emphasize the nuanced nature of these relationships, highlighting the pivotal role of the Fashion Industry as a mediator in the influence of Influencer Marketing on Brand Enhancement. This research contributes valuable insights for businesses, suggesting that strategic investments in influencer marketing can play a significant role in shaping brand perceptions within the dynamic landscape of the fashion industry. Keywords: Marketing Strategies, AI Technology, Enhancing Brand Awareness, Fashion Industry